Enhancing Quality of Life and Reducing Analgesic use with Targeted Nerve Blocks in Patients who are not Medically Fit for the Knee Arthroplasty: An Observational Study - Dareen Al-Mehman; Shahad Alkhashrami; Mujeeb Ashraf (Bali Journal of Anesthesiology, 2025)
Background: Total knee arthroplasty (TKA) has proven to be one of the most successful surgical treatments for end-stage osteoarthritis. However, certain patients are deemed unfit for arthroplasty. This study aimed to ascertain whether targeted peripheral nerve blocks could enhance quality of life, reduce the need for analgesic medication, and enhance mobility and function. Patients and Methods: This prospective cohort and qualitative research included 50 patients over the age of 50 years, either waiting or unfit for TKA. Genicular nerve block (GNB) was carried out using 14 mL of bupivacaine 0.25% and 40 mg methylprednisolone and adductor canal block (ACB) using 9 mL of bupivacaine 0.25% and 20 mg methylprednisolone. Results: The numeric rating scale (NRS) for pain significantly lowered after 2 weeks, 3 months, and 6 months compared to scores at the beginning of treatment (P < 0.001). Oxford Knee Score was significantly higher after 2 weeks, 3 months, and 6 months compared to scores at the beginning of treatment (P < 0.001). Health-Related Quality of Life and Outcome scores started to improve in just 2 weeks after commencing the treatment and continued to improve over the coming months. The daily analgesia requirements showed a significant reduction in 11 patients, a decrease in 5 patients. Conclusion: Targeted peripheral nerve blocks for patients either waiting for total knee replacement or those who are unfit for total knee replacement offer an excellent choice in improving the quality of life, increasing mobility, and reducing daily analgesia consumption with a reasonable satisfaction of patients with the procedure.